Identification of genetic modifiers of CagA-induced epithelial disruption in Drosophila - Reid, David W.; Muyskens, Jonathan B.; Neal, James T.; Gaddini, Gino W.; Cho, Lucy Y.; Wandler, Anica M.; Botham, Crystal M.; Guillemin, Karen (Frontiers in Cellular and Infection Microbiology, 2012)
Helicobacter pylori strains containing the CagA protein are associated with high risk of gastric diseases including atrophic gastritis, peptic ulcers, and gastric cancer. CagA is injected into host cells via a Type IV secretion system where it activates growth factor-like signaling, disrupts cell-cell junctions, and perturbs host cell polarity. Using a transgenic Drosophila model, we have shown that CagA expression disrupts the morphogenesis of epithelial tissues such as the adult eye. Here we describe a genetic screen to identify modifiers of CagA-induced eye defects. We determined that reducing the copy number of genes encoding components of signaling pathways known to be targeted by CagA, such as the epidermal growth factor receptor (EGFR), modified the CagA-induced eye phenotypes. In our screen of just over half the Drosophila genome, we discovered 12 genes that either suppressed or enhanced CagA's disruption of the eye epithelium. Included in this list are genes involved in epithelial integrity, intracellular trafficking, and signal transduction. We investigated the mechanism of one suppressor, encoding the epithelial polarity determinant and junction protein Coracle, which is homologous to the mammalian Protein 4.1. We found that loss of a single copy of coracle improved the organization and integrity of larval retinal epithelia expressing CagA, but did not alter CagA's localization to cell junctions. Loss of a single copy of the coracle antagonist crumbs enhanced CagA-associated disruption of the larval retinal epithelium, whereas overexpression of crumbs suppressed this phenotype. Collectively, these results point to new cellular pathways whose disruption by CagA are likely to contribute to H. pylori-associated disease pathology.